Aluminum Electrode Insulation Dynamics via Interface Oxidation by Reactant Diffusion in Organic Layers. Issue 23 (26th August 2018) - Fluhr, Daniel; Züfle, Simon; Muhsin, Burhan; Öttking, Rolf; Seeland, Marco; Roesch, Roland; Schubert, Ulrich S.; Ruhstaller, Beat; Krischok, Stefan; Hoppe, Harald
Abstract : Appreciable progress has been achieved in the development of organic photovoltaics (OPV) over the last decade. However, further improvement of operational stability remains a challenge. In this contribution, focus is placed on corrosion and delamination of the metal contact, which are mainly caused by oxygen or water vapor ingress but in other cases also via mechanical wear and different thermal expansion coefficients. So‐called pinholes and electrode edges provide pathways for ingress of water vapor and oxygen, which may attack the metal–organic interface. Thus, electrical insolation via formation of insulating metal oxide and concomitant mechanical delamination occurs. As charge injection and extraction is suppressed at insulated and delaminated areas, the active area contributing to power conversion gets reduced. This work links analytical and numerical predictions about the active area in contact with the electrode to experimentally observe dependencies. Spatially and time‐resolved electroluminescence measurements provide information on location, size, and growth‐rate of insulated areas. Area loss rates for dark spots depend either sub‐linear (for early stages and edge‐ingress) or linear (later stages) on time. The initial defect size has a clear impact on growth rates. Furthermore, it has possible to demonstrate titanium oxide interlayers to slow down this type of extrinsic degradation. Abstract : The diffusion of humidity and oxygen into non‐encapsulated organic solar cells with aluminium back electrode is studied. Novel aspects include the combination of numerical finite element simulations with analytical solutions to describe all observed diffusion phenomena, as well as a custom build automated analysis of experimental observations is used. In addition, it was shown that titanium oxide slows down device degradation.